Transdermal Delivery of Antigenic Protein Using Ionic Liquid-Based Nanocarriers for Tumor Immunotherapy - Uddin, S. (American Chemical Society, 2022)
Transdermal drug delivery systems (TDDSs) may be useful for preventing various diseases including cancer. However, the stratum corneum (SC) inhibits the permeation of foreign particles into the skin. To obtain an effective TDDS, we developed a protein-containing nanocarrier (PCNC) comprising an antigenic protein (ovalbumin/OVA) stabilized by a combination of surfactants, i.e., a lipid-based surface-active ionic liquid and Tween-80. The PCNC was lyophilized to remove water and cyclohexane and then dispersed in isopropyl myristate. It is biocompatible both in vitro and in vivo, and is suitable for use in a therapeutic TDDS. The skin permeability of the PCNC was significantly (p < 0.0001) enhanced, and the transdermal distribution and transdermal flux of the OVA delivery system were 25 and 28 times greater, respectively, than those of its aqueous formulation. The PCNC disrupted the order of lipid orientation in the skin's SC and increased intercellular protein delivery. It demonstrated effective antitumor activity, drastically (p < 0.001) suppressed tumor growth, increased mouse survival rates, and significantly (p < 0.001) stimulated the OVA-specific tumor immune response. The PCNC also increased the number of cytotoxic T cells expressing CD8 antibodies on their surfaces (CD8 + T-cells) in the tumor microenvironment. These findings suggest that PCNCs may be promising biocompatible carriers for transdermal antigenic protein delivery in tumor immunotherapy. Â© 2022 American Chemical Society.